1988
DOI: 10.1007/bf00539576
|View full text |Cite
|
Sign up to set email alerts
|

Hydatidosis in camels in Kuwait

Abstract: Infection of indigenous camels, Camelus dromedarius, with hydatid cysts has been recorded for the first time in Kuwait. From February 1982 to April 1983, 293 camels slaughtered for human consumption were examined. The overall rate of infection was 39.6%: 18.5% in animals less than 6 years old, and between 40.1% and 45.2% in older animals. The infection rate in females (44.9%) was significantly higher than in males (24.7%). Females also showed higher susceptibility to infections in multiple organs (22.7%) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
4
14
2
Order By: Relevance
“…The prevalence of hydatidosis was found to be significantly higher in female camel than the male (OR 2.8, P \ 0.05). This finding is in line with the reports of Salih et al (2011) and Gizachew et al (2013) from Ethiopia, and Abdul- Salam and Farah (1988)from Kuwait. This might be related to the practices keeping female camel around the homesteads at the backyard for milk production purpose.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of hydatidosis was found to be significantly higher in female camel than the male (OR 2.8, P \ 0.05). This finding is in line with the reports of Salih et al (2011) and Gizachew et al (2013) from Ethiopia, and Abdul- Salam and Farah (1988)from Kuwait. This might be related to the practices keeping female camel around the homesteads at the backyard for milk production purpose.…”
Section: Discussionsupporting
confidence: 93%
“…Such similarities in the prevalence of hydatidosis in the different locations of the country might be related to similarities in livestock health practices and associated risk factors among the communities of the study areas. Relatively higher prevalence of camel hydatidosis were reported from Ethiopia (Gizachew et al 2013), and elsewhere in the world (Abdul-Salam and Farah 1988;Ibrahim and Craig 1998;Ahmadi 2005;Mohamed 2010). The present study showed that lung was more frequently infected (57.6 %) than the liver (30.4 %).…”
Section: Discussionmentioning
confidence: 91%
“…This resultwas higher than the findings of Wubet (1987), Abdul-Salam (1988), Woldemeskel (2001), Ahmadi (2005), Bitsat (2009) and Mohammed (2010). The high prevalence in the present study could be due to the presence of high population of dogs which are closely associated with livestock in the field and barn as well as due to high population of wild carnivores in the area of the majority camels origin (Borena) (Balako, 1999) and due to lack of proper condemnation of organs infected with hydatidcyst in pastoral areas (Bekele, 2008).…”
Section: Discussionmentioning
confidence: 53%
“…Prevalence was higher in locally bred livestock than imported animals. In the late 1980s, CE was found in 39.6% of camels in Kuwait with higher pulmonary infection (63%) and higher cyst fertility than the hepatic cysts (Abdul-Salam and Farah, 1988). Updated information is required from other countries in the Arabian Peninsula.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%